Coach yourself to success : - Moglia, Joe (J. Wiley, 2005)
Knowing how to make money and hold onto your money has never been easy. Joe's strategies are clear, accessible, and performance based. Joe, thanks for taking the mystery out of investing. Leave it to Joe to look out for the rest of us Joes and Joannes. Practical. Useful. Meaningful. The man who democratized trading has now leveled the playing field. Joe Moglia has provided a coach's playbook for everyone. This is an invaluable tool for executing the right investing moves to win the game.